The predictive value of total-body PET/CT in non-small cell lung cancer for the PD-L1 high expression - Hu, Bingxin; Jin, Huibin; Li, Xiali; Wu, Xinyu; Xu, Junling; Gao, Yongju (Frontiers in Oncology, 2022)
Purpose：Total-body positron-emission tomography/ computed tomography (PET/CT) provides faster scanning speed, higher image quality and lower injected dose. To compensate the shortcomings of the maximum standard uptake value (SUVmax), we aimed to normalize value of PET parameters by liver and blood pool SUV (SUR-L and SUR-BP) to predict programmed cell death-ligand 1(PD-L1) expression in non-small cell lung cancer patients (NSCLC). Materials and methods: Total 138 (104 adenocarcinoma and 34 squamous cell carcinoma) primary diagnosed NSCLC patients who underwent 18F-FDG-PET/CT imaging were analyzed retrospectively. Immunohistochemistry analysis (IHC) was performed for PD-L1 expression on tumor cells and tumor-infiltrating immune cells with 22C3 antibody. Positive PD-L1 expression was defined as tumor cells no less than 50% or tumor-infiltrating immune cells no less than 10%. The relationship between PD-L1 expression with PET parameters (SUVmax, SUR-L and SUR-BP) and clinical variables were analyzed. Statistic analysis include χ 2 test, receiver operating characteristic (ROC) and binary logistic regression. Results: There were 36 patients(26%) expressing PD-L1 positively. Gender, smoking history, Ki-67 and histologic subtype were related factors. SUVmax, SUR-L and SUR-BP were significantly higher in positive subset than in negative. Among them, the area under curve(AUC) of SUR-L on ROC curve was the biggest one. In NSCLC patients, the best cut-off value of SUR-L for PD-L1 positive expression was 4.84(AUC=0.702,P=0.000, sensitivity=83.3%, specificity=54.9%). Multivariate analysis confirmed age and SUR-L were correlated factors in ADC patients. Conclusion: SUVmax, SUR-L and SUR-BP had utility in predicting PD-L1 high expression and SUR-L was the most reliable parameter. PET/CT can offer reference to screen patients for first-line atezolizumab therapy.